2021
DOI: 10.1016/j.bbih.2021.100268
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and gustatory dysfunctions in SARS-CoV-2 infection: A systematic review

Abstract: Background Among Coronavirus Disease 2019 (COVID-19) manifestations, Olfactory (OD) and Gustatory (GD) Dysfunctions (OGD) have drawn considerable attention, becoming a sort of hallmark of the disease. Many have speculated on the pathogenesis and clinical characteristics of these disturbances; however, no definite answers have been produced on the topic. With this systematic review, we aimed to collect all the available evidence regarding the prevalence of OGD, the timing of their onset and their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 181 publications
(218 reference statements)
2
62
0
Order By: Relevance
“… 1 , 83 86 Finally, objective methodology to assess olfactory dysfunction may be more sensitive than subjective recall, resulting in an increased prevalence, although studies are controversial. 7 Response bias may occur if early studies did not inquire about olfactory dysfunction as much as later studies.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 83 86 Finally, objective methodology to assess olfactory dysfunction may be more sensitive than subjective recall, resulting in an increased prevalence, although studies are controversial. 7 Response bias may occur if early studies did not inquire about olfactory dysfunction as much as later studies.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
“… 1 , 7 , 93 Some studies using objective tests showed an increase in the prevalence of olfactory dysfunction, 1 , 2 , 82 , 93 − 95 while other studies reported the opposite (reviewed in Boscutti et al, 2021). 7 In the studies on South Asian COVID-19 patients, objective tests were used in only three of the cohorts with G614 virus dominance. To avoid methodology as a confounding variable, we considered only studies with subjective questioning.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
“…1,[83][84][85] Finally, objective methodology to assess olfactory dysfunction may be more sensitive than subjective recall, resulting in an increased prevalence, although studies are controversial. 7 Response bias may occur if early studies did not inquire about olfactory dysfunction as much as later studies.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
“…1,7,93 Some studies using objective tests showed an increase in the prevalence of olfactory dysfunction, 1,2,82,[93][94][95] while other studies reported the opposite (reviewed in Boscutti et al, 2021). 7 In the studies on South Asian COVID-19 patients, objective tests were used in only three of the cohorts with G614 virus dominance. To avoid methodology as a confounding variable, we considered only studies with subjective questioning.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
See 1 more Smart Citation